Congestive heart failure arising from diastolic dysfunction in the presence of normal left-ventricular systolic function. - Stainback, R F (1999)
Congestive heart failure due to diastolic dysfunction is a common clinical entity, particularly in the elderly. As outlined, such patients fall into a larger group of all patients with CHF symptoms and normal systolic function. When finding "normal" systolic function, the clinician should embark upon a carefully outlined diagnostic work-up geared toward eliminating confounding or treatable contributing causes of dyspnea or typical CHF symptoms. The prognosis for CHF patients with primarily diastolic dysfunction is not as poor as for those with LV systolic dysfunction, although the prevalence, associated morbidity, and costs are great. In contrast to the large number of successful clinical trials that have guided treatment of LV systolic failure, an extremely limited number of trials have specifically addressed themselves to diastolic dysfunction. Marked symptomatic relief can often be provided with careful attention to tailored therapy, although little is known with regard to outcome. Refinements in noninvasive imaging methods and hemodynamic indices of diastolic function may lead to improved patient care.